Implementasi Pembelajaran Daring Menggunakan Aplikasi Google Classroom Pada Materi Menulis Teks Prosedur Siswa Kelas XI IPA 1 SMA Negeri 1 Tanah Grogot Kabupaten Paser - Syam, Yuswiarizky Nabilah; Sulistyowati, Endang Dwi; Elyana, Kukuh (Adjektiva: Educational Languages and Literature Studies, 2018)
This research was conducted at a school that implements online learning using the Google Classroom application, namely SMA Negeri 1 Tanah Grogot. During this pandemic, the learning process requires the right media so that learning activities can run effectively. This study aims to (1) describe the form of the learning implementation plan (RPP) used in the procedure text material, (2) describe the implementation of online learning using the Google Classroom application in the procedure text writing material, (3) describe the evaluation system applied in online learning. using the Google Classroom application for writing procedure text materials. 4) describe the advantages and disadvantages experienced when implementing online learning using the Google Classroom application at SMA Negeri 1 Tanah Grogot. This research is a qualitative research. Data collection techniques used are observation, interviews, and documentation. Data analysis techniques used are data collection, data reduction, data presentation, and conclusions. The results showed that 1) SMA Negeri 1 Tanah Grogot used the online 2013 curriculum RPP. The components of the lesson plans used are incomplete. Such as time allocation, indicators of competency achievement, learning media, and learning resources. 2) The implementation of online learning using the Google Classroom application went quite smoothly. However, it is not fully in accordance with the RPP used. Because there are some learning steps that are not carried out as written in the lesson plan. 3) Evaluation of learning given in the form of description questions. Students are asked to make a complex procedure text and determine the structure of the text and its linguistic elements. 4) The advantages are that the application is easy to use and the uploaded files are safe. The drawback is that the application display is too monotonous so that it seems boring.